EFFECT OF BOAR PRESENCE ON THE REPRODUCTIVE PERFORMANCE OF SOWS - S. Ramakrishnan; K.S. Sebastian; P.C. Saseendran; Joseph Mathew (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The success and efficiency of pig farming mainly depends on the reproductive performance of pigs. An experiment was conducted to study the effect of presence of the boar on the reproductive performance of sows, the feasibility and economics of rearing pigs of either sex together. Sixteen weaned Large White Yorkshire gilts, twelve weaned sows and two boars were randomly assigned to five groups as T1, T2, T3, T4 and T5 each consisting of six. Sows in T1 and T3 groups were bred at the body weight of 70-80 kg with designated boars at the time of breeding. The sows in T5 group were bred in the first oestrus after weaning. In T2 and T4 group sowswere reared with boar. The onset and intensity of oestrus were significantly different (p < 0.05) between groups. However, post weaning oestrus, duration of oestrus, conception rate and gestation length did not vary significantly between groups. Litter size and weight at weaning also did not vary significantly. The behaviour of parents and other pen mates towards the litter did not vary significantly (p > 0.05) in all groups. Overall results suggest that in farming conditions group housing system can be practiced. It isadvisable to keep animals in advanced stage of pregnancy in farrowing pens till weaning of piglets.